2022
DOI: 10.1073/pnas.2110776118
|View full text |Cite
|
Sign up to set email alerts
|

Volatile-consuming reactions fracture rocks and self-accelerate fluid flow in the lithosphere

Abstract: Hydration and carbonation reactions within the Earth cause an increase in solid volume by up to several tens of vol%, which can induce stress and rock fracture. Observations of naturally hydrated and carbonated peridotite suggest that permeability and fluid flow are enhanced by reaction-induced fracturing. However, permeability enhancement during solid-volume–increasing reactions has not been achieved in the laboratory, and the mechanisms of reaction-accelerated fluid flow remain largely unknown. Here, we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Other limitations to our models concern the omission of detailed sedimentary history (i.e., timing and availability of reservoirs and seals), as well as detailed natural H2 migration pathways to these reservoirs (e.g., 21; 22). In this context, the impact of density changes during serpentinization also requires attention, since the volumetric expansion of serpentinizing mantle material may either clog water and hydrogen pathways (52) or induce new fracturing and increase permeability (67). Finally, H2 gas is highly reactive and may easily be consumed by (bio)chemical reactions on its way to, or within reservoirs (e.g., 57; 68).…”
Section: Nuances To Our Model Analysismentioning
confidence: 99%
“…Other limitations to our models concern the omission of detailed sedimentary history (i.e., timing and availability of reservoirs and seals), as well as detailed natural H2 migration pathways to these reservoirs (e.g., 21; 22). In this context, the impact of density changes during serpentinization also requires attention, since the volumetric expansion of serpentinizing mantle material may either clog water and hydrogen pathways (52) or induce new fracturing and increase permeability (67). Finally, H2 gas is highly reactive and may easily be consumed by (bio)chemical reactions on its way to, or within reservoirs (e.g., 57; 68).…”
Section: Nuances To Our Model Analysismentioning
confidence: 99%
“…www.nature.com/scientificreports/ chemical weathering (e.g., carbonation and serpentinization) is widely observed in nature [69][70][71] . However, it is a major challenge to reproduce reaction-driven fracture propagation in a lab setting 72,73 . Uno et al 72 studied the hydration of periclase to brucite under confining pressure experimentally in a lab setting.…”
Section: Case 1: Single Edge Notched Tension Test (Without Reactive T...mentioning
confidence: 99%
“…However, it is a major challenge to reproduce reaction-driven fracture propagation in a lab setting 72,73 . Uno et al 72 studied the hydration of periclase to brucite under confining pressure experimentally in a lab setting. The volume-increasing hydration reaction resulted in fracture development and enhanced fluid flow.…”
Section: Case 1: Single Edge Notched Tension Test (Without Reactive T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments on a serpentinization-analogue system, involving the hydration of periclase to brucite (MgO + H 2 O → Mg(OH) 2 ), have demonstrated that under conditions of high reaction rates and low pore-fluid connectivity, hydration reactions may increase permeability by approximately three orders of magnitude (Uno et al 2022 ) and reaction-induced stresses could potentially reach gigapascal-levels (Plümper et al 2022 ). These findings differ from previous flow-through serpentinization experiments, which showed a decrease in permeability over several orders of magnitude, mainly caused by the clogging of fluid pathways due to mineral precipitation (Godard et al 2013 ; Farough et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%